2023
DOI: 10.1038/s43016-023-00795-w
|View full text |Cite
|
Sign up to set email alerts
|

Vegans, vegetarians, fish-eaters and meat-eaters in the UK show discrepant environmental impacts

Abstract: Modelled dietary scenarios often fail to reflect true dietary practice and do not account for variation in the environmental burden of food due to sourcing and production methods. Here we link dietary data from a sample of 55,504 vegans, vegetarians, fish-eaters and meat-eaters with food-level data on greenhouse gas emissions, land use, water use, eutrophication risk and potential biodiversity loss from a review of 570 life-cycle assessments covering more than 38,000 farms in 119 countries. Our results include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…We use two time dummies interchangeably: Period j , where j indicates the period of the experimental trial, such that j ä [1][2][3][4], and week k , where k indicates the week of the experimental trial, such that k ä [1-5] as indicated in table 1 above. Further for period 3, we use two treatment dummies, nudge+ 1 and nudge+ 2, which would take the value 1 if a participant i was assigned to either of the nudge+ conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use two time dummies interchangeably: Period j , where j indicates the period of the experimental trial, such that j ä [1][2][3][4], and week k , where k indicates the week of the experimental trial, such that k ä [1-5] as indicated in table 1 above. Further for period 3, we use two treatment dummies, nudge+ 1 and nudge+ 2, which would take the value 1 if a participant i was assigned to either of the nudge+ conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Current meat-based diets are carbon-intensive [1] and incompatible with Paris Climate targets [2]. Recent studies indicate that meat-consumption continues to increase globally [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, important local differences in the GHGE linked to specific foods may still exist and can impact the validity of our estimates. Future studies using more comprehensive GHGE estimations, such as those recently published by Scarborough et al [ 26 ], will increase our understanding of the contribution of the food systems to total GHGE. Second, we assumed the GHGE contribution of each food was the same over time since there is no information on the dietary carbon footprint for different years.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 35% of the U.S. corn production was used to make ethanol in 2022 (U.S. Department of Energy, 2023), but the demand for ethanol will decrease as the use of electric vehicles increases. Reductions in animal-based foods driven by utilization of plant-based meat substitutes (Mansky, 2019;Munson, 2021), "meat" produced in culture systems (Stephens et al, 2018), "eggs" produced from pea (Pisum sativa L.) protein (Munson, 2021), eating insects (Hazarika & Kalita, 2023), and shifting to a more plant-oriented diet (Clark et al, 2020;Ivanovich et al, 2023;Scarborough et al, 2023) will also reduce the demand for corn (much of the current production is fed to animals) and soybean meal (fed to animals as a protein supplement). Development of insectbased systems to produce protein from waste materials to feed animals (Hansen et al, 2023;Kupferschmidt, 2015) has the potential to further reduce the demand for soybean meal.…”
Section: Crop Sciencementioning
confidence: 99%